2001
DOI: 10.1002/ijc.10099
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant‐antioxidant status in relation to survival among breast cancer patients

Abstract: The role of plasma oxidant-antioxidant status in survival after breast cancer surgery was investigated in a cohort of patients (n ‫؍‬ 363) hospitalized in Southern France between 1989 and 1992. The median follow-up was 8 years after surgery for histologically confirmed breast cancer. Plasma analyses were performed after diagnosis and before surgery and adjuvant therapy. We found an inverse relationship between plasma lipoperoxides (MDA) and tumor size at diagnosis, together with higher lipoperoxide levels in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…However, even in the context of multiple compounds given at normal dietary doses, studies have found an increase in skin cancers in women [105,106] and prostate cancers in men who had high levels of PSA [107]. These observations are in line with the association of high levels of vitamin E and poor relapse-free survival in breast cancer [108] and to the findings of the SELECT study showing an increase in prostate cancer in the group treated by vitamin E [109]. A possible mechanism would be an anti-apoptotic effect of vitamin E as has been demonstrated in animal models [110].…”
Section: Carotenoidssupporting
confidence: 72%
“…However, even in the context of multiple compounds given at normal dietary doses, studies have found an increase in skin cancers in women [105,106] and prostate cancers in men who had high levels of PSA [107]. These observations are in line with the association of high levels of vitamin E and poor relapse-free survival in breast cancer [108] and to the findings of the SELECT study showing an increase in prostate cancer in the group treated by vitamin E [109]. A possible mechanism would be an anti-apoptotic effect of vitamin E as has been demonstrated in animal models [110].…”
Section: Carotenoidssupporting
confidence: 72%
“…However, lipoperoxides were not significantly associated with breast cancer-specific mortality (>0.5 lmol/L = 1.60 [0.73-3.51]). 48 In 2010, Sova et al reported that negative 8-oxodG tumor status based on immunohistochemistry was associated with lower breast cancer-specific survival (BCSS). 49 This study also reported that serum 8-oxodG, from blood collected before surgery, was not associated with BCSS, but data were not shown.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the timing of biomarkers varied, with some studies measuring markers before surgery, after surgery and before/during chemotherapy, and after any cancer treatments. The largest and earliest study reported a positive association between a marker of lipid damage and prognosis 48 ; however, this study used a marker of lipid peroxidation known to be nonspecific. Other studies generally reported limited evidence for an association.…”
Section: Biomarkers Of Oxidative Stress and Breast Cancer Prognosismentioning
confidence: 99%
“…Another study established that above-normal serum concentrations of vitamin E had a negative effect on breast cancer patients [68].…”
Section: Vitaminsmentioning
confidence: 99%